Immunohistochemical characterization of Sertoli cell tumour in an adult bull - SHARMA, SONU; GUPTA, R P; JANGIR, B L; HAZARI, RAGINI; LATHER, DEEPIKA (The Indian Journal of Animal Sciences, 2021)
The present study reports a case of Sertoli cell tumour and its immunohistochemical characterization using pancytokeratin, vimentin and p53 in an adult bull. A six and a half years old bull was presented in the Department of Veterinary Clinical Complex, College of Veterinary Sciences of the University with the history of gradual enlargement of both testes since last one and a half years. Grossly, both testes appeared hard and firm. Microscopically, haematoxylin and eosin stained tissue sections revealed neoplastic Sertoli cells arranged in groups as islands/broad sheets separated by connective tissue stroma. Neoplastic cells showed indistinct cytoplasmic boundary, cytoplasmic vacuolation and enlarged pleomorphic hyperchromatic nuclei with prominent nucleoli. Neoplastic cells were positive for p53 and vimentin and negative for pancytokeratin. Moderate to strong p53 nuclear immunoreactivity was noticed in most of the neoplastic cells indicating role of p53 tumour suppressor gene in tumourogenesis. Vimentin immunopositivity was observed in cytoplasm of neoplastic cells but no immunoreactivity for pancytokeratin was noticed. The application of pancytokeratin and vimentin antibodies in present case provided important information for differential diagnosis between Sertoli cell tumour and seminoma.